Input management in dairy co-operatives of Ollukkara Block - George Thomas (Department of Co- operative Management, College of Co- operation, Banking and Management, 1994)
The study entitles input Management in Dairy Co-operatives of Ollukkara Block was undertaken to examine the input management of dairy co operatives, identify the farmers preference for input services, and identify the problems as also constraints in input management by dairy co operatives.